Bridging the Gap: Using Consensus to Explore Entrustment Decisions and Feedback Receptivity in Competency-Based Emergency Medicine Residency Programs Through the Construction of a Q-Sample Incorporating a Delphi Technique - Chang, Yu-Che; Chuang, Renee S.; Hsiao, Cheng-Ting; Khwepeya, Madalitso; Nkambule, Nothando S. (Frontiers in Medicine, 2022)
Background Recent changes in medical education calls for a shift toward student-centered learning. Therefore, it is imperative that clinical educators transparently assess the work-readiness of their medical residents through entrustment-based supervision decisions toward independent practice. Similarly, it is critical that medical residents are vocal about the quality of supervision and feedback they receive. This study aimed to explore the factors that influence entrustment-based supervision decisions and feedback receptivity by establishing a general consensus among Taiwanese clinical educators and medical residents regarding entrustment decisions and feedback uptake, respectively. Methods In Q-methodology studies, a set of opinion statement (i.e., the Q-sample) is generated to represent the phenomenon of interest. To explore the factors that influence entrustment-based supervision decisions and feedback receptivity, a Q-sample was developed using a four-step approach: (1) literature search using electronic databases, such as PubMed and Google Scholar, and interviews with emergency clinical educators and medical residents to generate opinion statements, (2) thematic analysis and grouping using The Model of Trust, the Ready, Wiling, and Able model, and the theory of self-regulated learning, (3) translation, and (4) application of a Delphi technique, including two expert panels comprised of clinical educators and medical residents, to establish a consensus of the statements and validation for a subsequent Q-study. Results A total of 585 and 1,039 statements from the literature search and interviews were extracted to populate the sample of statements (i.e., the concourse) regarding entrustment-based supervision decisions for clinical educators and feedback receptivity emergency medicine residents, respectively. Two expert panels were invited to participate in a Delphi Technique, comprised of 11 clinical educators and 13 medical residents. After two-rounds of a Delphi technique, the panel of clinical educators agreed on 54 statements on factors that influence entrustment-based supervision decisions and were categorized into five themes defined by the Model of Trust. Similarly, a total of 60 statements on the factors that influence feedback receptivity were retained by the panel of medical residents and were categorized into five themes defined by the Ready, Willing, and Able model and the theory of self-regulated learning. Conclusion Though not exhaustive, the key factors agreed upon by clinical educators and medical residents reflect the characteristics of entrustment-based supervision decisions and feedback receptivity across specialties. This study provides insight on an often overlooked issue of the paths to teaching and learning in competency-based residency training programs. Additionally, incorporation of the Delphi technique further adds to the existing literature and puts emphasis as an important tool that can be used in medical education to rigorously validate Q-statements and develop Q-samples in various specialties.